Singular Value Decomposition based Phi Domain Equalization for Multi-Carrier Communication System - Aboltins, A.; Misans, P. (Elektronika ir Elektrotechnika, 2012)
Phi transform provides flexible way for construction of basis functions with desired parameters. This feature makes it highly eligible for utilization in multi-carrier communication systems. This paper is devoted to the problem of construction of an algorithm, which is capable to mitigate inter-block interference in Phi transform based communication system. Single equalization method and several channel estimation algorithms are proposed and their performance is compared. Simulation results of communication systems with various combinations of signal structure and channel estimators are presented and compared. DOI: http://dx.doi.org/10.5755/j01.eee.18.9.2811